Immune privilege in the subretinal space and prospects of retinal pigment epithelium transplantation in degenerative diseases of the retina - N. V. Neroeva; N. V. Balatskaya; L. A. Katargina; A. G. Brilliantova (Российский офтальмологический журнал, 2023)
Damage of the retinal pigment epithelium (RPE) underlies the pathogenesis of degenerative-dystrophic diseases of the retina, in particular, age-related macular degeneration (AMD) — one of the leading causes of irreversible loss of central vision, blindness and elderly population disability. Advanced AMD treatment options are limited to angiogenesis inhibitors in the wet form of the disease; there is no effective treatment for geographic atrophy, since RPE cells are unable to regenerate. The advances of biomedicine and the progress of vitreoretinal surgery gave rise to searching new high-technology methods of degenerative retinal disease treatment, aimed at restoring RPE. Replacement transplantation with induced pluripotent stem cells (iPSCs) specifically oriented at RPE seems to be the most promising approach for replacing damaged retinal elements and improving visual acuity, while, as some researchers believe, the fact that the eye is an immune-privileged organ ensures relatively safe conditions for subretinal administration of iPSC-RPE. The review systematizes the literature data on immune privilege in the posterior eye segment, as well as the results of studies in the field of subretinal stem cells transplantation. The conditions and possible mechanisms that trigger graft rejection, methods aimed at preventing tissue incompatibility reactions are also discussed.